The Believing Personality: Its Characteristics and Educational Impacts from a Qur'anic Perspective A Descriptive Study - Hussein, Prof. Dr. Ahmad Rashid Hussein; Kanu, Prof. Dr. Ali Abdul Kanu Abdul (Sulaimani Journal for Humanities, 2026)
The study of personality has occupied an important position, and what has helped confirm this position is the view of personality as the sum of several factors working in an integrated unit resulting from the interaction of several physical and psychological traits that determine the way a person deals with the components of his environment. Personality in the Holy Quran is closely linked to the inner workings of the soul, so he was the first to point out what positive psychology has pointed out today: that we need a formula for the Islamic personality in light of the Holy Quran, instead of vacillating between different schools of psychology. Our problem today is that we have lost our distinct personality and have begun to vacillate and waver between many personality traits, except for the faithful personality whose features have been outlined by the Holy Quran through its perfect evidence. Therefore, Allah Almighty has explained in the Holy Quran the types of people and drawn an illustrative picture for each type so that the visions of the faithful person are not confused. We wanted to say in this research that we need to re-understand every characteristic of the human personality in light of the Quranic text so that we can regain our effectiveness in society, preserve our identity, and improve our worldly management as we were before. We divided the research into an introduction, three chapters, and a conclusion. In the introduction, we explained the importance of this research and the question that this research wanted to answer. In the first chapter, we talked about the concept of personality and character in the Holy Quran. The second chapter was made to talk about the characteristics of the faithful personality in the Holy Quran, dividing it into two requirements: the first requirement for the concept of the faithful personality, the second for the characteristics of the faithful personality, and the third chapter for the educational effects of the faithful personality. The conclusion came to indicate the most important results and recommendations that this research came out with.
Keywords: personality; believer; education; Quranic perspective; description